'I'm not the only person out there': insider and outsider understandings of autism. (1st July 2013) - Jones, Robert S P; Huws, Jaci C; Beck, Gerhard
<x xml:space="preserve">Abstract</x> Objectives: The objective of this study was to gain an insight into how people with autism spectrum disorder (ASD) view the concept of autism and how they view society's reactions to people with this diagnosis. Methods: Nine students attending a specialist college for individuals with an ASD were interviewed about their views on the nature of autism. Once an initial qualitative analysis of their views had been completed, the analysis was sent to a person with autism and that person's secondary analysis was also included in the present paper. Results: The results suggested an awareness of the complexity of interpersonal relationships, a desire to 'fit in' to a wider group, and a feeling of being regarded as 'different'. The use of an expert author helped avoid a 'diagnostic overshadowing' interpretation of these findings, and located them as an interaction of age, life stage, and the presence of an ASD. Discussion: The use of an 'expert author' is a novel use of a qualitative methodology and specifically aided in the interpretation of the participant accounts.